Operative treatment of calcified thoracic disc herniation: a case report on natural fusion method following spinal canal decompression - Jelača, Bojan; Lasica, Nebojša; Golubović, Jagoš; Pajičić, Filip; Bijelović, Milorad; Djilvesi, Djula (Vojnosanitetski pregled, 2024)
Introduction. The literature describes several ways to approach the thoracic spinal segment, but there are still many dilemmas regarding what is best to do after a complete discectomy, regardless of the surgical approach chosen. The incidence of postoperative kyphosis is higher if a posterior surgical approach to the spine is performed, and there are no clearly defined indications for the application of intervertebral fusion (IF) after an anterior ap-proach. The aim of the paper was to highlight the low morbidity of the transthoracic multidisciplinary approach, as well as a potential solution for a good, natural IF of the adjacent vertebrae without expanding and prolonging the duration of the surgical procedure itself. Case report. A 44-year-old woman presented with severe anterior compressive myelopathy caused by a calcified thoracic disc herniation in the space between the T10-11 vertebrae. A minimally invasive, open, transthoracic approach was performed with decompression of the spinal canal at the specified level and IF was achieved with an autologous rib graft during the same procedure. Despite the relatively low incidence of postoperative spinal instability, one should not overlook a good chance to achieve IF and prevent long-term complications. A control examination of the thoracolumbar segment using the magnetic resonance imaging showed that there is no more compression of the spinal cord and also showed a good IF without an increase in the level of kyphosis. Conclusion. Significant thoracic disc herniation is a rare and challenging surgical lesion. The anterior mini-open transthoracic approach provides good exposure to the relevant structures and is considered minimally invasive. The benefits of subsequent IF after the transthoracic surgical approach should always be taken into account for each individual patient, thus minimalizing the postoperative morbidity.